Service Learning Program In Konsulat Jendral Republik Indonesia (KJRI)-Johor Bahru, Malaysia - Satriadi Satriadi; Vandi Verdiansyah; Anggraini Diah Hardaya Putri; Rachmad Chartady; Jati Hari Winarto; Cindy Mayrianti (International Journal of Community Engagement and Development, 2024)
Indonesia is a country that has various kinds of customs, tribes and cultures. Many Indonesian citizens work in Malaysia to improve its economy. However, many Indonesian migrant workers have problems in Malaysia, such as being treated inappropriately. The service activities carried out by STIE Pembangunan Tanjungpinang students were 14 students and 2 accompanying lecturers. Service activities were carried out at the Consulate General of the Republic of Indonesia (KJRI)- Johor Bahru, Malaysia on October 29th, 2023. The method used was participatory. The Indonesian Consulate General is a government agency to protect Indonesian citizens abroad, one of which is the Indonesian Consulate General in Johor Bahru, Malaysia. Many Indonesian migrant workers become victims of human trafficking. There are also many Indonesian migrant workers who enter Malaysia without complete administrative evidence and without correct procedures or not in accordance with the recommendations of the law.